Factors Affecting Patient Satisfaction With Their Anesthesiologist: An Analysis of 51, 676 Surveys From a Large Multihospital Practice. (October 2019) - Pozdnyakova, Anastasia; Tung, Avery; Dutton, Richard; Wazir, Anum; Glick, David B.
Abstract : BACKGROUND: An increasing focus of health care quality is the assessment of patient-reported outcomes, including satisfaction. Because anesthesia care occurs in the context of perioperative surgical care, direct associations between anesthetic management and patient experience may be difficult to identify. We analyzed anesthesia-specific patient satisfaction survey data from a large private practice group to identify patient, procedure, and anesthetic-specific predictors of patient satisfaction with their anesthesiologist, measured via responses to a validated patient satisfaction survey instrument. We hypothesized that some factors governing satisfaction with an anesthesia provider are beyond their ability to control. METHODS: We retrospectively reviewed responses to the Anesthesia Patient Satisfaction Questionnaire (APSQ), administered online to patients cared for by US Anesthesia Partners, a multistate anesthesia group practice. The APSQ focuses on patient satisfaction with their anesthesiologist and patient-reported outcomes and is administered after discharge. Responses from May to November 2016 were aggregated, and relationships between responses and patient, procedural, and clinician-related factors were assessed using multivariable logistic regression. RESULTS: Out of 629, 220 adult patients cared for during the study period, 51, 676 responded to the survey request for a 9.3% overall response rate for patients. Nonresponders were slightly older and more likely to be male than responders. After multivariable regression, no patient or procedural factor was associated with patient rating of their anesthesiologist. However, ≥55 years of age, inpatient (versus outpatient) setting, and nighttime surgery (between 6 PM and 6 AM) were associated with lower scores on other satisfaction questions. CONCLUSIONS: Our data suggest that some factors governing satisfaction with an anesthesia provider are beyond their ability to control. Further work is needed to identify elements of patient satisfaction with their anesthesiologist and to optimize these aspects of perioperative care.